FLARE STARS IN THE PLEIADES REGION 1971 1972 III - HARO, G; CHAVIRA, E (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1971)
During the months of October, November and December, 1971 and January, 1972 we obtained 115 ultraviolet multiple exposure plates centered in Alcyone and covering an area of approximately 16 square degrees. There were 725 different exposures with a total t
BOL OBS TONAN TACUB
Keywords: FLARE, STARS, PLEIADES, REGION, 1971, 1972; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS